Dampak Psikologis dalam Memberikan Perawatan dan Layanan Kesehatan Pasien COVID-19 pada Tenaga Profesional Kesehatan - Lilin Rosyanti; Indriono Hadi (Poltekkes Kemenkes Kendari, 2020)
Stress and anxiety are reactions to threatening and unpredictable situations such as in a coronavirus pandemic outbreak. Health workers are the most vulnerable to this. Stress-related reactions include changes in concentration, irritability, anxiety, insomnia, reduced productivity, and interpersonal conflict, in subsequent cases, they will experience more severe psychiatric conditions, separation from family, abnormal situation, increased exposure, increased exposure exposure, fear of transmission of COVID-19, feeling of failure in handling a poor prognosis, inadequate technical facilities, PPE, tools and equipment, to help treat patients. Health workers have difficulty maintaining physical and mental health conditions that are at risk of experiencing psychological disorders such as depression, anxiety, severe stress, and fatigue. Other risk factors identified are feelings of being unsupported, concerns about personal health, fear of bringing infections and transmitting them to family members or others, isolated, feeling uncertain, social stigmatization, excessive workload, and feeling insecure when providing care and health in COVID -19 patients.